VLF/LF Reflectivity of the Polar Ionosphere, 2 January-30 April 1977 - Rasmussen,John E; Turtle,John P; Pagliarulo,Robert P; Klemetti,Wayne I (1977)
This report provides a summary of high latitude ionospheric reflectivity as observed by the USAF high resolution VLF/LF ionosounder operating in northern Greenland. Ionospheric reflectivity parameters, including reflection heights and coefficients, are presented as a function of time of day. VLF long path propagation measurements, along with magnetometer and riometer data, are presented as supplementary information. (Author)